Non-Implementability of Arrow-Debreu Equilibria by Continuous Trading Under Knightian Uncertainty - Frank Riedel; Patrick Beissner (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
Under risk, Arrow-Debreu equilibria can be implemented as Radner equilibria by continuous trading of few long-lived securities. We show that this result generically fails if there is Knightian uncertainty in the volatility. Implementation is only possible if all discounted net trades of the equilibrium allocation are mean ambiguity-free.
Keywords: D81; C61; G11; 330; Knightian Uncertainty; Ambiguity; General Equilibrium; Asset Pricing; Radner Equilibrium